Escola complementar e normal de Piracicaba: formação, poder e civilidade (1897-1921) - Honorato, Tony [UNESP] (2011)
This thesis is a research about the history of Complementary and Normal School of Piracicaba, figures modeled in training primary school teachers within the State of São Paulo. Searched as was the historical process of Complementary and Normal School of Piracicaba (1897-1921). It was aimed to interpret the constitution of the Schools of Piracicaba as figurations, to characterize teacher training as a reference and demonstrate civilizing power relations based on the elements of school culture. The theoretical and methodological procedures fell on the proposal of Norbert Elias, particularly Figurational Sociology and Theory of Civilizing Processes. It was elected, as a primary source historical manuscripts, printed papers and legislation. The period defined between 1897 and 1921 justifies its inception in 1897 by the introduction of Complementary Piracicaba and its end because its transformation into Normal School, which was considered as a reference in the context of the Reformation of 1920, given its educational and cultural effervescence caused by a group of teachers and intellectuals linked to Sampaio Dória. It was concluded that, in addition to producing the image of modern man and civilized society in Republican figurations Piracicaba lived along its historical balance of power in a network of schools to train teachers, thus implying a further reduction of power the prestigious Escola Normal da Capital